Sistem Informasi Perpustakaan pada Dinas Perpustakaan dan Kearsipan Daerah Kabupaten Sumba Barat Daya - Ensi Dabi Tamar; Cecilia Dai Payon Binti Gabriel; Mitra Permata Ayu (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
The library is a place to get information through books that have been provided by the Southwest Sumba Regency Library and Archives Office. The problem faced by researchers is when books have not been neatly arranged on the shelves and many books have not been archived in an application so researchers design an application to assist in making a computer-based system. The library information system application is designed with the PHP programming language and MySql as a database. From the results of this study, the library information system can be used as expected and can help officers manage book data and borrower data easily.